The future of cloud computing in improving employee productivity among Small and Medium-sized Enterprises (SMEs) in Johor - Azhar, Nur; Rodzalan, Shazaitul (Universitas Muhammadiyah Yogyakarta, 2022)
Cloud computing has been recognized as one of the digital transformations that play a vital role in the twenty-first century. With various benefits of the implementation in organizations, cloud computing has become a trend for international organizations. In recent years, the interest in migrating to cloud computing has been more emphasized due to the benefits and opportunities it offers in improving and enhancing the quality and productivity of an organization. Unfortunately, cloud computing is still new in Malaysia. There is lacking of previous studies mainly in the context of cloud computing in Malaysia. Thus, the main focus of this study is to identify the issues and drivers of cloud computing and to study the future trend of cloud computing in improving employee productivity among SMEs in Johor. This study was mixed-method research that used both qualitative and quantitative methods. For the qualitative method, STEEPV analysis was used to identify the drivers of cloud computing. A total of 147 drivers were found after STEEPV analysis, and 10 of the merged drivers found incorporated into the survey questionnaire. This study achieved the research objectives which are to identify the key drivers and to study the future trend of cloud computing in improving employee productivity among SMEs in Johor. The top two drivers were increase market and customer segmentation and flexible payment. Finally, this research gives significant benefits to future researchers and those organizations that implement cloud computing in business as this study provides evidence of the most influential drivers of cloud computing in improving employee productivity.